Perpetual Persistence: The African American Community of Manhattan Bottoms, 1880-1920 - Latchman-Hall, Blake (Kansas State University, The Chapman Center for Rural Studies, 2014)
Using the case study of Jeremiah "Jerry" Mitchell, this study documents the early history of Manhattan Bottoms and the African American community located there.
Blake Hall-Latchman, “Perpetual Persistence: The African American Community of Manhattan Bottoms, 1880-1920,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/235.
Keywords: African American history; butcher; Manhattan; Manhattan Bottoms; Riley County; Jim Crow